Los Cantorales mozárabes de Cisneros - Carmen Julia Gutiérrez (Mélanges de la Casa de Velázquez, 2019)
The Hispanic liturgy, supposedly maintained by the Mozarabic community of Toledo, has been considered a testimony of an alleged national identity since the Middle Ages, because it represents the old Visigothic Christianity. For this reason, this liturgy has been insistently restored by ecclesiastical power, surviving periods of neglect and even having been forgotten. This text shows the process of the most important of these restorations, the one of cardinal Cisneros: Cisneros had to reconstruct and adapt the texts of the neo-Mozarabic liturgy, but also its melodies. Some of these melodies were taken from the oral tradition of the community, but for others it was necessary to invent a melodic tradition based on a system of formulas. The formulas used were few, simple and repetitive, and they managed to create a style identified as «Mozarabic», which has since been considered the true reflection of the Visigothic tradition.